Near-surface soil heat flux and evaporation dynamics using heat pulse probes - Parajuli, Sudipti (My University, 2025)
Evaporation is an important component of the soil water balance. Accurate and dynamic measurements of evaporation are important to identify water management practices that minimize evaporation losses and increase agricultural productivity. Most of the existing methods for quantifying soil evaporation do not provide depth-resolved information on near-surface evaporation dynamics. This thesis explores the potential of applying the sensible heat balance (SHB) method to quantify the temporal and spatial patterns of sub-surface evaporation using field-based experiments. The first chapter of this thesis focuses on determining soil thermal properties and heat balance components using three-needle heat pulse probes. The study investigates the prospects of heat pulse probes in determining near-surface soil heat flux and heat storage using millimeter-scale measurements of soil temperature and thermal properties. The second chapter examines the performance of the sensible heat balance method to estimate near-surface soil evaporation by comparing it with evaporation measurements from the Eddy Covariance (EC) and microlysimeter methods. Temporal and spatial analysis of soil sensible heat flux demonstrated that heat flux densities decreased in magnitude with depth, and temperature gradient was the major factor influencing heat flux. Change in soil sensible heat storage showed lower values at all depths as compared to heat flux. Good agreement (R² = 0.62) was observed between evaporation from the SHB and EC methods, whereas no correlation was seen between evaporation estimates from the SHB and microlysimeter methods. Overall, our findings show the potential of the SHB method for fine time (30 min) and depth (mm) scale measurements of evaporation.
Keywords: Sensible heat balance; Heat pulse probe; Evaporation